Effects of endurance training on capillary density and energy metabolism of the right ventricle of streptozotocin –diabetic swine: the role of HIF and AMPK behind changes - Alkio, Milla (fi=Turun yliopisto|en=University of Turku|, 2017)
Diabetes affects 422 million people all over the world. Its special characteristic is hyperglycemia that eventually leads to coronary artery disease and diabetic cardiomyopathy. Exercise training is known to enhance cardiovascular fitness and function in which hypoxia inducible factor (HIF) has an important role. Therefore, the purpose of this M.Sc. thesis was to determine if exercise training can reduce the possible adverse effects of diabetes, including reduced capillary density and defective energy metabolism of Göttingen minipig right ventricle. To study this, the activities of citrate synthase (CS), lactate dehydrogenase (LDH), and β-hydroxyacyl CoA dehydrogenase (HOAD) were measured spectrophotometrically, the protein levels of HIF, vascular endothelial growth factor (VEGF), AMP-activated protein kinase (AMPK), and pAMPK were determined with Western blotting, and histological methods were used to measure the capillary densities and cardiomyocyte cell sizes. Diabetes alone decreased cardiomyocyte size in the diabetic animals, whereas the combination of exercise training and diabetes resulted in an increased level of AMPK and increased activity of LDH and HOAD. When AMP/ATP ratio becomes unbalanced, AMPK is activated and more ATP is produced e.g. by enhancing the uptake of fatty acids into the mitochondria. This was shown indirectly with increased activity of HOAD. LDH also helps maintaining the ATP levels when aerobic metabolism cannot function efficiently due to lack of oxygen. In conclusion, although diabetes itself did not affect the energy metabolism of the untrained animals, in trained animals the metabolism was changed through AMPK, which helps securing the animal’s energy needs during exercise training situation.